Childcare and Child Development Surveillance: Challenges for Comprehensive Child Healthcare - Renata Aparecida Dornelas Silva; Karine de Jesus Mourão; Ana Elisa Costa Cunha; Clarice Moreira de Oliveira Gonçalves; Márcia Aparecida Silva Araújo; Sérgio Raimundo Ernesto Machado; Elis Vânia Marques de Matos; Ivanice de Fátima Ribeiro (RSV, 2026)
Childhood represents a critical period for human development, requiring healthcare approaches capable of promoting physical growth, emotional well-being, cognitive development, and social adaptation. In this context, childcare and child development surveillance constitute essential strategies within Primary Health Care for ensuring comprehensive monitoring of children's health trajectories. These practices extend beyond disease prevention and clinical evaluation, incorporating early identification of developmental risks, promotion of healthy environments, family guidance, and coordination of multidisciplinary interventions. Despite advances in child health policies, several challenges continue to affect the implementation of comprehensive childcare models. Inequalities in access to healthcare services, limitations in professional training, fragmented care practices, and insufficient integration between health, education, and social protection sectors may compromise timely identification of developmental needs. Strengthening childcare requires approaches that recognize childhood as a multidimensional process influenced by biological, family, social, and environmental factors. This academic essay analyzes the role of childcare and child development surveillance in promoting comprehensive healthcare for children. The discussion explores the importance of Primary Health Care, multidisciplinary practices, early intervention strategies, and public policies aimed at strengthening child health. The manuscript argues that effective childcare requires integrated healthcare networks capable of combining prevention, monitoring, health promotion, and social support to ensure adequate developmental opportunities for all children.